HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN SUBJECTIVE WELLBEING (SWB) PADA PENDERITA KANKER DI IRNA BEDAH RSUP DR. M. DJAMIL PADANG TAHUN 2016 - Ns, M.Kep, Zuriati S.Kep, (Menara Ilmu, 2017)
Cancer is a disease which if after continuation stadium difficult to in curing. At cancerpatient can result worriing, depression, position negativistik ( rejection) what relating tosatisfaction of life even prosperity (Subjective Well-Being). Initial survey which researcherdoes in three rooms, got 7 people between it is telling less happyly and feels hopeless. While 3people tells often is assisted family in experiencing everyday life. Purpose of this research is toknow the relation of family social support from with Subjective Well-Being (SWB) at cancerpatient in IRNA Bedah RSUP Dr. M. Djamil Padang the year 2016. This research haves thecharacter of analytic with design cross sectional which has been executed in IRNA BedahRSUP Dr. M. Djamil Padang in January - August 2016. Population of all cancer patient inKelas, Bedah Wanita and Bedah Pria RSUP Dr. M. Djamil Padang in Oktober-Desember 2014amounts to 150. Sampling technique in all cancer patient in Kelas, Bedah Wanita and BedahPria RSUP Dr. M. Djamil Padang in Oktober-Desember 2014 amounts to 150 with number ofsamples 38. Data is collected to applies questionaire and analysed to applies analysis univariatand bivariate with statistic test chi-square. Result of research is got (60,5%) patient hasSubjective Well-Being (SWB) low. (52,6%) patient gets unfavourable family social supportfrom. There is the relation of family social support from with Subjective Well-Being (SWB) atcancer patient (p = 0,024). Based on phenomenon is upper, inferential that there is the relationof family social support from with Subjective Well-Being (SWB) at cancer patient, henceexpected that the side of hospital is more increases quality of treatment service in hospital,especially for cancer patient focusing at approach efekstifity of family by giving counsellingand procedural information cures cancer to cancer patient family.Keywords : Subjective Well-Being, Family Social Support, Cancer